The Importance of Family Dinners - Jodimae Lyttle; Eboni J. Baugh (EDIS, 2008)
FCS-2286, a 2-page fact sheet by Jodimae Lyttle and Eboni J. Baugh, takes a close look at some family “dinner dynamics” sharing research demonstrating the benefits that eating together can provide family members. Published by the UF Department of Family Youth and Community Sciences, August 2008.